A Particular Silhouette of Human-Influenced Coconut Trees in Hindu Bali, Indonesia: An ethnobotanical field note - Miyaura, Rie; Ohno, Tomoko; Maenaka, Hisayuki; Sumiartha, Ketut; Yamaguchi, Hirofumi (Ethnobotany Research and Applications, 2015)
In Hindu Bali, coconut trees near human settlements exhibit a particular silhouette. To understand the relationship between human activity and the landscape created by plant usage, we analyzed the extent of the cut-leaved coconut canopies and consumption pattern of coconut leaflets for religious purposes on Bali Island. Cut-leaved coconut canopies were identified in 78% of the 18 sites investigated, and 22% of coconut trees had cut leaves. Coconut leaflets, young and old, were gathered from live trees and frequently used for many offerings such as canang, penjor, and sanggah cucuk for Dewi Sri as part of plant decorations made with various colorful flowers and ornamental tree leaves. Balinese people still make traditional offerings with intact plant materials, although recently coconut leaflets are increasingly sold in markets in urban areas. We conclude that this particular coconut silhouette is a result of human ritual activities stemming from the Balinese culture.